Loyalty Model In Umrah Religious Tourism Travel and Factors that Influence It (Study on Ajwa Tours Indonesia) - Yuliani, Weni; Syafrizal , Syafrizal; Lenggogeni , Sari (eScience Humanity Journal, 2024)
Study This aim For analyze the model and influencing factors loyalty and satisfaction Ajwa Tours Indonesia Umrah congregation. Loyalty and satisfaction are crucial success a company in give service to customer. Population sample in study This is Umrah pilgrims who have use Ajwa Tours Indonesia services 2 years the latest (2022-2023) as many as 200 customers. Study This use analysis description through SmartPLS 4.0. The variable being measured are social media marketing, brand image, and service quality, satisfaction and loyalty. Research result show that the Social Media Marketing variable has an influence positive and not significant on satisfaction and loyalty. Brand Image has an influence on loyalty and satisfaction positive and significant. Satisfaction has an influence on loyalty positive However No significant. Service quality has an influence on satisfaction positive and significant. Service quality has an influence on loyalty positive No significant. And satisfaction has an influence on loyalty positive and significant.